Positive experience with TNF-α inhibitor in toxic epidermal necrolysis resistant to high-dose systemic corticosteroids - Nikitina, Ekaterina A.; Fomina, Daria S.; Markina, Ulyana A.; Andreev, Sergey S.; Streltsov, Yuri V.; Kruglova, Tatiana S.; Lebedkina, Marina S.; Karaulov, Alexander V.; Lysenko, Maryana A. (Frontiers in Medicine, 2023)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare, potentially life-threatening syndromes characterized by the development of necrotic epidermal and mucosal lesions. The most common etiologic cause of SJS/TEN is drug-induced mechanisms. The group of drugs with high potential risk includes sulfonamides, anticonvulsants, nonsteroidal anti-inflammatory drugs (NSAIDs), allopurinol, phenobarbital, etc. There is no gold standard treatment algorithm for SJS/TEN. In medical practice, systemic glucocorticosteroids (sGCS), intravenous immunoglobulin (IVIG), plasmapheresis, and cyclosporine are used empirically and in various combinations. Recently published studies have demonstrated the efficacy of TNF-α inhibitors as a promising approach in SJS/TEN, including cases resistant to high-dose sGCS, with etanercept and infliximab being the most commonly used drugs. In a large multicenter study by Zhang J et al, 242 patients treated with etanercept and/or sGCS combination had lower mortality compared to the control group. Shorter skin healing time was documented compared to sGCS monotherapy, thus reducing the risk of secondary infections. The published data show a high efficacy with THF-α inhibitor blockade, but the safety of TNF-α inhibitors in patients with SJS/TEN is still questionable due to the paucity of available information. As all clinical research data should be accumulated to provide reliable evidence that the use of TNF-α inhibitors may be beneficial in SJS/c, we report a case of etoricoxib-associated SJS with progression to TEN in a 50-year-old woman who was refractory to high-dose sGCS therapy.